Distribution, incidence and farmers knowledge of banana Xanthomonas wilt in Burundi - Ndayihanzamaso, P.; Niko, N.; Niyongere, C.; Bizimana, S.; Nibasumba, A.; Lepoint, P.C.E.; Tinzaara, William; Kaboneka, S.; Sakayoya, E.; Jogo, W.; Mugiraneza, T.; Karamura, E.B. (Academic Journals, 2016)
Banana Xanthomonas wilt (BXW) is a devastating bacterial disease caused by Xanthomonas campestris pv. musacearum. The disease was simultaneously reported in Cankuzo and Bubanza provinces, Burundi, in November 2010. However, the extent to which the disease has spread to other banana growing regions in the country is unknown. Therefore, to ascertain the distribution and incidence of the disease and farmers’ knowledge on measures to control the disease, a survey was conducted in all 16 banana growing provinces of Burundi in August 2011. A total of 208 farms were sampled, selecting six farms per surveyed commune, three affected and three non-affected. The survey was conducted using a structured questionnaire. The disease was present in 10 out of 16 provinces constituting all agricultural lands in Burundi. The highest incidence was recorded in Ruyigi province (34%), where the Kayinja system is dominant and the lowest in Muyinga (3%), where the East African Highland bananas (EAHB) dominate. Awareness of BXW symptoms, modes of spread and control measures was generally low, ranging from 8 to 30% of households surveyed. The limited knowledge of the disease among farmers was thought to be largely responsible for driving the epidemic in Burundi.